The Study Of The Peculiarities Of The Psychological Perception Of The Karabakh War In 2020 - Yeribekyan, Benik
Տեղեկույթի շարունակական փոփոխությունը, դրա քանակական և որակական առանձնահատկությունների տարբերությունները մարդկային հոգեկանի առջև դնում են մի շարք խնդիրներ: Постоянно меняющийся поток информации, ее качественные и количественные особенности различия ставят перед человеческой психикой ряд насущных вопросов․ The constantly changing flow of information, its qualitative and quantitative differences pose a number of pressing questions to the human psyche.
Keywords: Psychology